Prevention Strategies for the Abuse of Psychoactive Plants - Suryansyah, Akhmad; Usmita, Fakhri (Sisi Lain Realita, 2026)
The abuse of psychoactive plants in Pekanbaru City has shown an increasing trend and poses a threat to public health due to low awareness, environmental influences, and easy access to plants with potential for misuse. This study aims to analyze the prevention strategies implemented by the National Narcotics Agency of Pekanbaru in 2025 using a qualitative method with a descriptive approach through observation, interviews, and documentation. The results indicate that prevention is carried out through three approaches: primary prevention through socialization and community empowerment, secondary prevention through law enforcement and assessment, and tertiary prevention through medical and social rehabilitation. These efforts still face challenges such as limited community participation and stigma toward victims, highlighting the need for strengthened education and cross-sector collaboration to ensure more effective and sustainable prevention.